MODÃËLE DÃ¢â¬â¢APPRENTISSAGE SCHÃâ°MATIQUE POUR AMÃâ°LIORER LA COMPÃâ°TENCE DE LA COMPRÃâ°HENSION ECRITE (SCHEMATIC-BASED LEARNING MODEL TO IMPROVE STUDENTSÃ¢â¬â¢ COMPETENCE IN READING COMPREHENSION) - Yulianto, Ahmad (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2012)
This article is an abstract of research conducted at French Language Department of Semarang State University. This research itself was intended to discover how far schemata (oneÃ¢â¬â¢s prior knowledge) influence ability in understanding a passage. Reading comprehension requires not only linguistic competence but also non-linguistic competence. It happens that one does not understand a passage notwithstanding his grammatical mastery. In this research, two groups of students were used as control and experiment classes respectively. With the help of t-test, pre-test score average and post-test average were compared and analyzed to find out whether or not schematic-based model gives rise to studentsÃ¢â¬â¢ reading performance.